Do Acquisitions Add Value to Acquirers in India? A Study on the Sensitivity of the Stock Market and Acquirer Returns - M., Maria Evelyn Jucunda; Sophia, Sharon (Indian Journal of Finance, 2014)
"Do acquisitions create value for the acquiring firm's shareholders?" This is an unresolved question in the literature of acquisitions. This study analyzes the value creation of acquirers in India on an acquisition announcement and the sensitivity of the stock markets during an acquisition announcement. Most of the literature in the West concludes that, on an acquisition announcement, only the targets create value, and the acquirers are value destructive. This study uses a sample of 78 acquirers in the manufacturing industry who acquired targets in the calendar year 2012. The study develops four hypotheses and uses the event study methodology (market model/ ordinary least square model). The results of the study suggest that acquisitions are neither value creative to Indian acquirers and those acquirers with prior acquisition experience create more value than single acquirers. Surprisingly, the results show that acquirers using cash generate negative returns, which may be due to the presence of the hubris effect. Another important finding of the study is that the acquirers using stock as a method of payment are no longer value destructive, which is contrary to the literature which states that acquirers using cash are value creative and acquirers using stock are value destructive. This is an important contribution to the existing literature of the method of payment, and it implies that the theories in the West may not necessarily hold well in India, and they need to be reassessed before being implemented in the Indian context.